Biological and physico-chemical formation of Birnessite during the ripening of manganese removal filters. (1st February 2015) - Bruins, Jantinus H.; Petrusevski, Branislav; Slokar, Yness M.; Huysman, Koen; Joris, Koen; Kruithof, Joop C.; Kennedy, Maria D.
Abstract: The efficiency of manganese removal in conventional groundwater treatment consisting of aeration followed by rapid sand filtration, strongly depends on the ability of filter media to promote auto-catalytic adsorption of dissolved manganese and its subsequent oxidation. Earlier studies have shown that the compound responsible for the auto-catalytic activity in ripened filters is a manganese oxide called Birnessite. The aim of this study was to determine if the ripening of manganese removal filters and the formation of Birnessite on virgin sand is initiated biologically or physico-chemically. The ripening of virgin filter media in a pilot filter column fed by pre-treated manganese containing groundwater was studied for approximately 600 days. Samples of filter media were taken at regular time intervals, and the manganese oxides formed in the coating were analysed by Raman spectroscopy, Electron Paramagnetic Resonance (EPR) and Scanning Electron Microscopy (SEM). From the EPR analyses, it was established that the formation of Birnessite was most likely initiated via biological activity. With the progress of filter ripening and development of the coating, Birnessite formation became predominantly physico-chemical, although biological manganese oxidation continued to contribute to the overall manganese removal. The knowledge that manganese removal in conventional groundwater treatment is initiated biologically could be of help in reducing typically long ripening times by creating conditions that are favourable for the growth of manganese oxidizing bacteria. Graphical abstract: Highlights: Filter media ripening started with formation of biological Birnessite (MnOx ). Birnessite was identified and characterized, with Raman spectroscopy, EPR and SEM. With prolonged time, Birnessite became predominantly of physico-chemical origin. With EPR and SEM biological and physico-chemical Birnessite could be distinguished.